Detecting 6 DoF geometrical errors of rotary tables. (1st March 2020) - Kniel, Karin; Franke, Matthias; Härtig, Frank; Keller, Frank; Stein, Martin
Highlights: Error detection in rotary tables integrated into coordinate measuring machines. Application of an error separation method called three-rosette method. Measurement of an uncalibrated circular ball plate in multiple positions. Verification with a 12-ball plate by determining all six error contributions. Abstract: An error separation method called three-rosette method allows all errors in rotary tables integrated into coordinate measuring machines (CMMs) to be determined by means of an uncalibrated circular ball plate. The calibration procedure takes advantage of the fact that error contributions can be separated and eliminated by means of multiple measurements of each ball center in well-defined measurement positions. The skilled evaluation of these results allows all six degrees of freedom (DoF) of a rotary table to be detected: the angular positioning error motion, the axial error motion and two error components for describing both the tilt error motion and the radial error motion. The method is of practical and economic relevance, as ball plates can be manufactured at low cost and require no further calibration. A detailed measurement and evaluation strategy as well as example results are presented.